Assessment of functional status in the elderly persons in the rural area of Punjab - Singh, Nirankar; Kumar, Shailendra; Muzammil, Khursheed; Raghav, Santosh Kumar; Singh, Jai Veer (Indian Journal of Community Health, 2014)
Research Question: What is the Functional Status in elderly people? Objective: To assess the Functional Statusof elderly people in rural area of Patiala District. Study Design: Cross-sectional descriptive study. Setting: Arural area of District Patiala- TheField Practice Area of Department of Community Medicine. Participants: 743 elderly people aged 60 years & above including 369 males and 374 females Study Variables: Elderly, Functional Ability. Statistical Analysis: Percentage, z-test Results: Out of 743 elderly persons, majority of study population(97.3%), were totally independent for physical activities of daily living (PADL), while rest 2.7% were dependent for one or more physical activities on others including total dependence of 0.5%. The inability in doing specific physical activity of daily living was highest in walking & transferring (3.8%). 3.5% of the study population was totally dependent and 84.6% of them were totally independent while rest 11.9% of them were dependent for their one or more instrumental activities of daily living (IADL) on others. Inability in doing specific instrumental activity of daily living was found to be highest for cooking (25.1%). Conclusion: The majority of subjects were independent for doing PADL & IADL activities, showing that they possessed more potential as compared with patients assessed by other studies.